Faith-based organizations, community development, and room of manoeuvre in gang controlled neighbourhoods in San Salvador - Chris van der Borgh (Journal of Illicit Economies and Development (JIED), 2020)
This paper aims to contribute to our understanding of the feasibility and effectiveness of development interventions in situations of chronic violence, paying particular attention to the capacity and room of manoeuvre of intervening organisations in contexts where illicit groups have built up a power position. It analyses the interventions of two faith-based NGOs (FBOs) that aim to reduce violence and promote community development in selected gang-controlled neighbourhoods of the Metropolitan Area of San Salvador (AMSS). Based on a literature study and data from fieldwork in several municipalities of the AMSS, it focuses on the ways the organisations navigate in extremely complex contexts. It is argued that the factors that contribute to the capacity of the FBOs to work in gang controlled neighbourhoods include their evangelical identity, the acceptance by and independence from gang and government, their longer-term engagement in selected neighbourhoods, and the combination of social interventions that have a local impact (education, healthcare) with the promotion of moral values. The paper also discusses some of the dilemmas and limitations of these kinds of approaches.
Keywords: 330; policy; chronic violence; gangs; NGOs; prevention